Wacana Kearifan Kapitalis dalam Dunia Postmodern: Tinjauan atas Kampanye One/Live 8 - Maliki, Musa (UI Scholars Hub, 2005)
The tension of postmodern condition creates two distinctive grand-narrative discourses in seeing poverty: modernist and anti-modernist. Even though the discourse of the postmodern condition remains within the regime of grand narrative discourses, there is a little narrative called the wisdom of capitalist discourse. It has been successful in the constructive active and non-violence resistance to make poverty history by ONE/Live 8 campaign. By the discourse's scheme, this study argues that the existence of poverty text is not the epistemological problem that can be solved exogenously by problem solving theory (grand theory), but it is the ontological problem that can be solved endogenously by constitutive theory. Here, the wisdom of capitalist discourse presented by ONE/Live 8 campaign, gives us an understanding that being human is being-with (Mitda-sein), not being-thing at hand (zuhandenes). If human beings can live being-with, the existence of poverty text will be history. In the nuance of being-with, human beings will achieve the highest stage of life, the authancity of self, the meaning of life, and construct a better world order.